Estudo anátomo-funcional por ressonância magnética em pacientes com epilepsia mioclônica juvenil - Lin, Katia [UNIFESP] (2009)
Purpose: The neuroanatomical basis and the neurochemical abnormalities that underlie juvenile myoclonic epilepsy (JME) are not fully understood. While the thalamus plays a central role in synchronization of widespread regions of the cerebral cortex during a seizure, emerging evidence suggests that all cortical neurons may not be homogeneously involved. The purpose of this study was to investigate the cerebral metabolic and structural differences between JME patients and normal controls. Methods: All patients had a JME diagnosis based on seizure history and semiology, EEG recording, normal magnetic resonance neuroimaging (MRI) and video-EEG according to the Commission on Classification and Terminology of the International League Against Epilepsy, 1989. Sixty JME patients (JME-P) were submitted to 1.5 T MRI multi-voxel proton spectroscopy and voxel-based morphometry (VBM). The control group consisted of 30 age and sex-matched healthy volunteers. The Institutional Ethics Committee approved the study, and informed consent was obtained from all participants. Results: Group analysis demonstrated lower N-acetyl-aspartate/Creatine (NAA/Cr) ratio among patients compared to controls on prefrontal, frontal cortices and thalamus. Patients had a statistically significant difference in glutamate-glutamine complex (GLX)/Cr on prefrontal and frontal cortices, insula, striatum and posterior cingulate gyrus. When evaluating the relationship among the various components of this epileptic network among JME-P, the strongest correlation occurred between thalamus and prefrontal cortex and a significant negative correlation between NAA/Cr and duration of epilepsy was found. Also, VBM demonstrated significantly reduced gray matter volume (GMV) in thalami, insula cortices and cerebellar hemispheres bilaterally; while significantly increased GMV was observed in right superior frontal, orbitofrontal and medial frontal gyri among JME-P when compared to controls. Conclusions: The identification of a specific network of neurochemical dysfunction and slight structural abnormalities in patients with JME, with diverse involvement of particular structures within the thalamocortical circuitry, suggests that cortical hyperexcitability in JME is not necessarily diffuse, supporting the knowledge that the focal/generalized distinction of epileptogenesis should be reconsidered and reinforcing the concept of ‘system epilepsies’.